Dirac Video Codec and Its Performance Analysis in Different Wavelet Bases - (:unkn) unknown (IEEE, 2016)
Dirac video codec was developed by BBC for advanced video applications as an open technology standard. Dirac aroused attention due to its relative simplicity and absence of license fees, and took a good place among high level video codec standards such as MPEG-2, H.264 and HEVC. In this paper, the Dirac video codec is investigated for different wavelet bases, and a new filter is proposed to increase its performance. Analyses are observed in PSNR and SSIM quality metrics.
Keywords: Dirac; PSNR; SSIM; H.264; WMV; HEVC; wavelet; biorthogonal